Analysis of the Factors Causing a Decline in Soil Quality and Their Solutions as an Effort to Increase Agricultural Productivity in Dry Areas - Muh Ansyar; Herdiana Herdiana (Jurnal Penelitian Pendidikan IPA, 2023)
West Nusa Tenggara (NTB) is an area that has abundant agricultural resources apart from the tourism sector. Generally, the climate in NTB is a tropical climate which is in the southern part of Lombok, namely in the Central Lombok area. The technique of determining the location and population was carried out using a purposive sampling method, meaning that the population used as a research sample was a population that met certain sample criteria according to the research objectives, and what had to be represented depended on the assessment or considerations of the researcher. Meanwhile, the data analysis used was descriptive data analysis quantitative with multiple linear regression analysis, t-test and F-test, and qualitative descriptive analysis using interview techniques with questionnaires, counseling, and FGD. The stages of the research are surveys, interviews, distribution of respondents, Forum Group Discussion (FGD), counseling, and evaluation. Land conversion, excessive use of pesticides and burning of crop residues was carried out on this basis by the Forum Group Discussion (FGD) which aims to provide solutions to existing problems. From the results of multiple in-ear regression SPSS testing, there is a significant relationship between the variable Y (level of agricultural productivity) in Pujut District and the factors that cause a decrease in soil quality or soil degradation (Variable X) that occurs at the research location with the results of the regression equation, namely Y = 5,398+ 0.97X1+0.125X2+0886X3+0.861X4. The results of the regression equation show a strong relationship between the decline in soil quality and the factors causing the decline in soil quality in the Pujut sub-district